1977
DOI: 10.1210/endo-100-5-1357
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Preferential Effects of Parathyroid Hormone, Calcitonin and Adenosine on Bone and Periosteum1

Abstract: In order to explore the distribution of hormone-responsive cells in skeletal tissues, we have examined the effects of synthetic bovine parathyroid hormone N-terminal peptide (bPTH 1-34) and salmon calcitonin (sCT) on cyclic AMP levels in periosteum-free rat calvaria, segments of periosteum, and in isolated cells dispersed from each tissue by collagenase digestion. Synthetic bovine PTH increased cyclic AMP levels to a greater degree in calvaria and in isolated bone cells than in the periosteal segments and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…Most of the evidence for this property is, however, circumstantial . A number of investigators have found high cAMP responses to PTH in isolated bone-cell populations where the osteoblasts were expected to be (13, 17,21,24). A more direct indication was provided by Davidovitch et al (5), who showed with immunohistochemical techniques that, in osteoblasts, cAMP can be stimulated by PTE .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the evidence for this property is, however, circumstantial . A number of investigators have found high cAMP responses to PTH in isolated bone-cell populations where the osteoblasts were expected to be (13, 17,21,24). A more direct indication was provided by Davidovitch et al (5), who showed with immunohistochemical techniques that, in osteoblasts, cAMP can be stimulated by PTE .…”
Section: Discussionmentioning
confidence: 98%
“…Several procedures have been used to obtain these different types of bone cell (13,17,20,21,23) . Generally, the isolated cells are cultured as a monolayer for a number of days and then used for biochemical studies.…”
mentioning
confidence: 99%
“…Because the stimulatory effect of IGF I on CDP labeling was opposedI by IBMX, a knowni inhibitor of cyclic AMP (cAMP) phosplhodliesterase (34), and by PTH, believed to acet onl bone by inereasing cAMP (14,23), it is possible that the effect of IGF I on collagen syntlhesis is medliatedl by a dlecrease in cAMP. This mechaniisnm has been proposed for other growtlh fhactors (35), but cAMP hals nlot been reportedl to h1ave a role mediatinig IGF effects in other tisstues or cell systemiis ancd the IGF I effeets on [3Hlthymidine incorporationi in bone were not altered by IBMX.…”
Section: Discussionmentioning
confidence: 99%
“…Additional analysis of the enzymatic content and responsiveness to PTH and CT suggested that the PT cells are osteoblasts (4). Independent studies in Peck's laboratory using a mechanical separation technique also showed that adenylate cyclase of -osteoblasts is activated by PTH and not by CT, whereas CT-stimulated production of cyclic AMP is observed in a separate cell population obtained from the periosteum (5). These important findings suggested to us the possibility that, by assay of the hormonally activated adenylate cyclases in developing bone tissue, it should be possible to delineate the temporal relationships for appearance of osteoblasts and osteoclasts and to define enzymatically the emergence of bone cells.…”
mentioning
confidence: 99%